2001
DOI: 10.1002/ppul.1123
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lung disease of the newborn is not associated with Ureaplasma urealyticum

Abstract: To clarify the association of Ureaplasma urealyticum infection with chronic lung disease of the newborn 145 preterm infants less than 34 weeks of gestation were examined. The infants were enrolled during two separate periods. The presence of U. urealyticum was studied by obtaining endotracheal culture samples and blood samples; if either of these samples grew the organism, the child was regarded as having U. urealyticum infection. Infection with U. urealyticum was detected in 33%, and chronic lung disease (def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 30 publications
0
6
1
1
Order By: Relevance
“…Studies in infants with mean birth weights of 827-1000 g demonstrated OR of 2.0 -3.8 (24,26 -28), yet in studies of larger infants (975-1300 g) there was no association detected between Ureaplasma sp. and BPD (14,33,35). This ambiguity may be related to the difference in size, as smaller, more gestationally immature infants are at higher risk of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in infants with mean birth weights of 827-1000 g demonstrated OR of 2.0 -3.8 (24,26 -28), yet in studies of larger infants (975-1300 g) there was no association detected between Ureaplasma sp. and BPD (14,33,35). This ambiguity may be related to the difference in size, as smaller, more gestationally immature infants are at higher risk of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…The studies were also grouped by definition of BPD, oxygen requirement at 28 days postnatal age (BPD28) and/or 36 weeks postmenstrual age (BPD36). Twenty-three articles reported Ureaplasma colonization and BPD28 (2,6,7,13,45,49,62,89,109,111,123,128,134,137,208,209,215,216,241,247,250,307,329) and eight reported BPD36 (49, 89, 109, 111, 127, 208, 209, 216). There were 2216 infants included in the BPD28 group and 751 infants in the BPD36 group.…”
Section: Association Of Ureaplasma Spp With Development Of Chronic Lmentioning
confidence: 99%
“…Meta‐analysis by Wang et al in 1995 found a significant association between U. urealyticum colonization and subsequent development of CLD 2 . Since then the association of CLD and U. urealyticum has been an issue for discussion and is still controversial 3–13 . This may be due to the different definitions of CLD used in varied studies, with differences including patient selection or sites and the time of sampling for the culture.…”
mentioning
confidence: 99%